Online Health Information Seeking Behaviour and Perceived Trust on Health Communication Channels among Undergraduate Students of Bangladesh: Online Health Information Seeking Behaviour - Rahman, Ashiqur; Lima, Nusrat Jahan; Nurunnabi, Abu Sadat Mohammad; Rukon, Rukonuzzaman; Hassan, Abid; Sultana, Hafiza (Journal of the Medical College for Women & Hospital, 2025)
Background: Health communication channels include traditional media like television, radio and print newspapers along with online newspapers and digital social media platforms like Facebook, YouTube, Twitter (X), and Blogs. The internet has become a valuable resource for accessing health information allowing individuals to actively engage in their health-related decision making. Objective: Our study aims to observe online health information seeking behaviour and perceived trust on those online health communication channels among the undergraduate level students of Dhaka City in Bangladesh. Materials & Methods: This cross-sectional study was conducted between January and December of 2023. A total of 384 students hailing from four institutions of Dhaka city namely Jagannath University, Daffodil International University, Enam Medical College and Mandy Dental College participated in this study. A pretested questionnaire was used for data collection, which included demographic characteristics, online health information seeking behaviour and perceived trust on those online health communication channels. For measuring perceived trust on online channels, the items were adopted from the Health Information National Trends Survey (HINTS) scale. Results: The majority (63%) of the study participants were ≥21 years old; the mean age was 20.98±1.18 years. 53.4% were males and 46.6% were females; male-female ratio was 1.5:1. 52% had medical/dental background. Most of the respondents used internet for health information within the week before survey (55.5%) and preferred digital channels (89%) over broadcast channels (11%) for health information. The mean of perceived trust on online channels was observed 3.13±1.64; online newspapers were the most trusted (3.03), while Facebook was the least trusted (2.41). Younger respondents aged ≤20 years reported higher perceived trust in online health information than those aged ≥21 years (P<0.05). A higher perceived trust was also observed among female students compared to male students (P<0.05). However, correlation of educational background and institutions with recent internet use did not show any statistically significant difference among the students (P>0.05). Those who preferred digital channels exhibit much greater levels of trust on those online channels compared to those who preferred broadcast channels (P<0.05). Conclusion: Undergraduate level students regularly use the internet and prefer digital channels over broadcast channels for health information. Online newspapers are found to be the most trusted among health communication channels. J Med Coll Women Hosp.2025; 21 (1):86-94